Quantitative investigation of influence of Al2O3 non-metallic inclusions on bending strength of powder metallurgy highspeed steel. Issue 1 (1st February 2022) - Hu, Qipeng; Chen, Yunbo; Wang, Miaohui; Ge, Xueyuan; Liu, Hengsan; Zuo, Lingli; Zhang, Dongyue
Abstract: The types, dimensions and quantities of inclusions have been examined to quantitatively investigate their influence on the bending strength and impact toughness of HIPed high-speed steel. MgSiO3 inclusion was found to be less harmful than Al2 O3 inclusion in terms of mechanical properties. Additionally, the inclusion of Al2 O3 of 0-20 μm under 0.02 vol.% showed a slight influence on the bending strength of certain HSS.